FURNITURE IN THE RENAISSANCE - BULGARIAN DESIGN OR NOT? - Parvanova, Aleksandrina (Innovation in Woodworking Industry and Engineering design, 2013)
Renaissance is a turbulent period of change, both economically and socially. Interior and furniture plays a big role socio-cultural environment. The design and taste of the Bulgarians are formed on the basis of already occurred European styles. Chair schools that have been appearing are trying to adjust our own culture to that which is modern in Europe during this dynamic period. Despite the difficulties faced with Bulgarian designer, he found a back door to national development in this area.